Sri Lanka’s Ministry of Indigenous Systems of Medicine - World Bank (Washington, DC, 2012)
Ayurveda and other traditional systems of health care have been used for over two thousand years in Sri Lanka. Indigenous systems such as Ayurveda are based on the country's cultural, social, economic, and religious characteristics. In addition, Sri Lankans utilizing knowledge of these indigenous systems of medicine were the first in the world to develop the concept of a hospital and established a highly scientific public healthcare system.